Checklist of Orthoptera Caelifera from Colombia - Carbonell, C. S.; Rowell, C. H.f.; Bentos-Pereira, A.; Porras, M. F. (Zootaxa, 2007)
The purpose of this list is to make known the species currently recorded from Colombia, with the aim of showing the present state of knowledge of the suborder ORTHOPTERA, CAELIFERA in this extraordinarily diverse country. The list has been derived from the unpublished Lista de Referencia de los Acridomorfos Neotropicales compiled by one of the present authors (C.S.C.), from which we have extracted the Colombian data. Other two authors have added data arising from their own work in Colombia and the fourth checked geographical names and the Von Humboldt collection.